The Moral Range of Political Duty - Idowu, Oladele Daniel (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
Political duty is either the central or fundamental problem of political philosophy. There is no doubt, however, that the history of political thought is replete with attempts to provide a satisfactory account of political duty from the time of Socrates to the present. To have a political obligation is to have a moral duty to obey the laws of one’s country or state. On that point, there is almost complete agreement among political philosophers. But how does one acquire such an obligation? Is political duty more a matter of being than of doing – that is, of simply being a matter of the country or state in question? Many answers have been proffered but none commands widespread assent. However, this study is an attempt to add to the existing debate, by suggesting a solution to the problem of political duty. The paper adopts expository and analytic approaches that are usually associated with philosophical scholarship. Indeed, a number of contemporary political philosophers deny that a satisfactory theory of political duty either has been or can be devised. Others, however, continue to believe that there is a solution to what is called ‘the problem of political obligation’, and they are presently engaged in lively debate not only with the skeptics but also with one another on the question of which theory, if any, provides the solution to the problem. We therefore, show that the political leader, in ensuring the peace and growth of the society, must consciously embrace morality. For morality and politics are bound together. Keywords: Duty, Justice, Morality, Philosophy, Politics,